Property Tax Limitation and Racial Inequality in Effective Tax Rates. (March 2017) - Martin, Isaac William; Beck, Kevin
In the late 20th century, two thirds of American states enacted policies to limit the growth of local property tax revenues. We examine the effects of property tax limitations on the effective property tax rates reported by homeowners of different racial and ethnic groups in the United States. We find that property tax limitations reduce the effective property tax rates of homeowners regardless of their race and ethnicity, but that most forms of property tax limitation exacerbate racial inequality, providing the greatest reduction in effective tax rates to white homeowners. In the aggregate, these inequalities result in substantially unequal tax savings that might not survive democratic scrutiny if they were distributed as direct subsidies. This inequality may be especially problematic insofar as tax privileges for property owners effectively disguise a public benefit as a private property right.